Case Report: A pediatric case of the clear-cell variant of mucoepidermoid carcinoma in the palate harboring MAML2 gene rearrangement - Wang, Hengkun; Wang, Xiaoya (Frontiers in Pediatrics, 2025)
The clear-cell variant of mucoepidermoid carcinoma (MEC) is a rare subtype, with pediatric cases being extremely rare. A 13-year-old girl presented with a lesion on the right palate, which had been noted for 3 months. The patient reported pain, rupture, and bleeding of the tumor for nearly a month. Computed tomography scans revealed a quasi-circular soft tissue mass on the right hard palate. Microscopically, the tumor cells showed predominant clear cells and scattered mucous cells. The tumor cells were positive for cytokeratin (CK), CK7, CK5/6, epithelial membrane antigen, P63, and P40. A rearrangement of mastermind-like transcriptional coactivator 2 (MAML2) (11q21) gene was identified in the tumor cells by fluorescence in situ hybridization. The histological features supported a diagnosis of clear-cell variant of MEC, medium grade, with a tumor stage of pT1N0M0. The patient underwent a complete excision of the palatal mass followed by superficial bone removal. After surgery, the patient recovered well and was recurrence-free at the 1-year follow-up. Based on repeated pathological evaluations, we report this rare pediatric case of a clear-cell variant of MEC of the palate. Only surgical resection resulted in a favorable outcome.